Effect of Li+ Doping on Photoelectric Properties of Double Perovskite Cs2SnI6: First Principles Calculation and Experimental Investigation - Jin Zhang; Chen Yang; Yulong Liao; Shijie Li; Pengfei Yang; Yingxue Xi; Weiguo Liu; Dmitriy A. Golosov; Sergey M. Zavadski; Sergei N. Melnikov (Nanomaterials, 2022)
Double perovskite Cs2SnI6 and its doping products (with SnI2, SnF2 or organic lithium salts added) have been utilized as p-type hole transport materials for perovskite and dye-sensitized solar cells in many pieces of research, where the mechanism for producing p-type Cs2SnI6 is rarely reported. In this paper, the mechanism of forming p-type Li+ doped Cs2SnI6 was revealed by first-principles simulation. The simulation results show that Li+ entered the Cs2SnI6 lattice by interstitial doping to form strong interaction between Li+ and I−, resulting in the splitting of the α spin-orbital of I–p at the top of the valence band, with the intermediate energy levels created and the absorption edge redshifted. The experimental results confirmed that Li+ doping neither changed the crystal phase of Cs2SnI6, nor introduced impurities. The Hall effect test results of Li+ doped Cs2SnI6 thin film samples showed that Li+ doping transformed Cs2SnI6 into a p-type semiconductor, and substantially promoted its carrier mobility (356.6 cm2/Vs), making it an ideal hole transport material.